EFEKTIFITAS PENYEBARAN PESAN AL-QURAN SEBAGAI KONTRIBUSI DALAM MEMBENTUK GENERASI QURANI - irfan yuhadi (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2018)
Al-Quran is a holy book that contains instructions for humans as well as distinguishing between good and evil. In the Quran there is an order to do good and there is also an order to stay away from various evils. Therefore, people who believe need to be remembered with messages in the Quran. In today’s modern era, ways to spread Al-Quran messages can be done through social media. Only a short time the messages of the Quran can be spread throughout the archipelago through their smart phones. The formulation of the problem in this study is about: (1) the concept of spreading the message of the Quran, (2) the effectiveness of spreading the message of the Quran, (3) suggestions in the spread of the message of the Quran to be more effective as a contribution in shaping the Quranic generation. The approach in this study is to use a qualitative approach.The results of this study indicate that: (1) Al-Quran messages were made by taking pieces of Al-Quran verses, then distributed to several coordinators spread across several cities in East Java through various social media facilities. (2) The spread of Al-Quran messages through social media is considered quite effective as a contribution in shaping generations. (3) Among the suggestions that the spread of the message of the Quran be more effective are: (a) Increase the theme of human relations, (b) Do not use language that is too formal, (c) the writing and drawing designs are improved.